PEMBANGUNAN, KAUM MISKIN KOTA, DAN AKTIVISME: STUDI KASUS PENGGUSURAN KAMPUNG KENTINGAN BARU, KOTA SOLO - Muhammad Aminullah Thohir (UNIVERSITAS SEBELAS MARET (UNS), 2024)
Development cannot be separated from the situation of the capitalist system. Ulrick Beck explains that development will lead to a society that has a high risk of life. Development with the concept of Neoliberalism will focus on economic growth. Urban development requires land, which can be obtained from evictions. The urban poor become vulnerable groups who are often affected by evictions. This situation makes people fight back against the injustice they experience. The people who live in Kampung Kentingan Baru are a picture of the evicted residents and fight back. This research uses Qualitative research method with Critical Ethnography approach. Data were collected through interviews, participant observation, direct observation, FGD, and document study. The results of this study illustrate that the people of Kentingan Baru live in high risk. They live in a cycle of evictions that is not just one-time, some residents have been evicted before living in Kentingan Baru. People who moved from Kentingan Baru also live in villages that are also threatened with eviction. Thus, the urban poor are in a perpetual cycle of eviction. The urban poor also have a low health risk because they live in inadequate housing after the eviction. When they resist, they are also threatened in the economic aspect because they are laid off or cannot work because they have to stand guard in the village when there is news of eviction and the security aspect where they often get intimidated.